Penetapan vitamin yang larut dalam lemak dengan kromatografi cair tekanan tinggi (KCTT)=The Analysis of Fat Soluble Vitamins by High Pressure Liquid Chromatography - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
ABSTRACT Qualitative and quantitative analysis of Fat soluble vitamins (vitamin Apalmitate, D2, E-acetate, and K) in Multivitamin powder have been performed by High Pressure Liquid Chromatography. The fat soluble vitamins were analysed by using Li-Chrosorb RP-8 column and UV-Spectrophotometer detector ( 270 nm). The following mobile phase was employed: methanol, methanol-ethanol mixture (5:2), and methanol-water mixture (95:5). The result indicated that the analysis using methanol as mobile phase (1 ml/ minute) gave 3 peaks identified as vitamin K, 1)2, and E-acelate, with 12 minutes time of analysis. A mixture of methanol-ethanol (5:2) as the mobile phase (1 ml/minute) gave 2 peaks identified as vitamin K and a mixture consisting of vitamin 1)2 and E-acetate, the time of analysis was 6 minutes. A mixture of methanol-water (96:6), on the other hand, could satisfactorily separate vitamin K., 1)2, E-acetate, and A-paimitate within 10 minutes. It can be concluded that methanol-water mixture is the best mobile phase for separation fat soluble vitamins. The. result of the application of this method to multivitamin powder gave (%): vitamin K (93,00 Â± 5,13)